The Influence of Green Accounting, Green Innovation, Environmental Performance and Sustainability Report on Company Value - Trisna Lailatul Elvia; Indri Kartika; Chrisna Suhendi; Dian Essa Nugrahini (Journal of Social Research, 2025)
Firm value reflects investor perceptions and is influenced by environmental, social, and governance (ESG) practices. Prior studies show conflicting results on how green initiatives impact company value, particularly in emerging markets like Indonesia. This study investigates the effects of green accounting, green innovation, environmental performance, and sustainability reports on company value in Indonesia’s basic and chemical industry sector (2021–2023). Using purposive sampling, 84 companies were analyzed via multiple linear regression (SPSS 27). Variables were measured through environmental cost disclosures (green accounting), PROPER ratings (environmental performance), and sustainability report indices. Green accounting and sustainability reports negatively affect company value, while green innovation has a positive impact. Environmental performance shows no significant effect. The model’s low Adjusted R² (0.142) indicates other unexplored factors. Companies should prioritize cost-efficient green innovations over symbolic disclosures. Policymakers may need to incentivize genuine sustainability efforts. Future research should expand sectors (e.g., energy) and incorporate variables like profitability to enhance explanatory power.